Effectiveness of the Use of the Human Recombinant Epidermal Growth Factor in the Subsidized Regime vs The Contributive Regime in Patients with Venous Ulcers in Bogotá - Cacua Sanchez MT; Buenahora G; Carrillo Bravo CA (Dove Medical Press, 2024)
Maria Teresa Cacua Sanchez,1 Gustavo Buenahora,2 Carlos Alberto Carrillo Bravo3 1Ambulatory Surgery Center, Kennedy Hospital, Vascular Laboratory SURA, Bogotá, Colombia; 2Hospital and Ambulatory Surgery Center, Bogotá, Colombia; 3Clinical Epidemiology - Colombian Society of Preventive Medicine, Bogotá, ColombiaCorrespondence: Maria Teresa Cacua Sanchez, Tel +57-1-3057470125, Email mcacua@gmail.comIntroduction: Vascular ulcers constitute a serious global public health problem, responsible for causing a significant social and economic impact due to their recurrent, disabling nature and the need for prolonged therapies to cure them.Objective: To evaluate the use and efficacy of the rhEGF in the epithelialization of patients with a diagnosis of CEAP stage 6 venous insufficiency, in the two regimes of the health system in Colombia, the contributive (equivalent to a health system where citizens with payment capacity contribute a percentage of their salary) and the subsidized (equivalent to a health system where the state covers the vulnerable population and low socioeconomic level) versus the other treatments used.Methodology: Observational, descriptive, retrospective, multicenter study, in which 105 medical records with 139 ulcers were reviewed, in 2 centers, one belonging to the subsidized system and the other to the contributive system in Colombia.Results: The association with the epithelialization variable of the different treatment groups for ulcers according to the application of the mixed effect model test, for both regimes was for the Biologicals (EC 34.401/p = 0.000), Bioactive Agents (Hydrogels) (EC 24.735/p = 0.005) groups; for the rest of the treatment groups, the results were neither associated nor statistically significant.Conclusion: Intra- and perilesional therapy with rhEGF expands the therapeutic spectrum in patients with venous ulcers, regardless of the type of health system in which it will be applied, shortening the healing time and reaching a possible therapeutic goal, which according to this study there is an association with epithelialization regardless of the regime applied.Keywords: venous ulcers, human recombinant epidermal growth factor, health system, contributive regime, subsidized regime, intralesional and perilesional